REVITALISASI DAYA TARIK WISATA BUDAYA DI DESA LINGGA KABUPATEN KARO - Jhonson Pardosi; Nurcahaya Bangun; Asmyta Surbakti; Samerdanta Sinulingga (Jurnal Pariwisata Pesona, 2019)
This research is motivated by the problem of the increasingly weak understanding of the Lingga Village community regarding the Lingga Traditional House. To overcome this, the research stages are aimed at: 1) knowing the tourist attractions contained in the Traditional House in Lingga Village. 2) to find out the shape of the Traditional House Revitalization model in Lingga Village. This research method uses phenomenological qualitative research methods. The results of this study are: 1) Lingga Traditional House can be said as a Tourist Attraction Spot because it has a Uniqueness, Beauty and Value. 2) The Revitalization Model of Traditional Houses in Lingga Village consists of 2 forms, namely the Conservation Form and the Economic Rehabilitation Form. For our next research we recommend reviewing the Opportunities and Challenges Analysis of the Establishment of Tourism Awareness Groups in Lingga Village as a technical step in implementing cultural revitalization in this location.